Effect of garlic and ginger extracts on the levels of glucose and Peptide-c in diabetic mice - Fadil, Hiam Kamel; Sheikh Yousef, Kholoud Mostafa (Journal of agricultural, environmental and veterinary sciences, 2021)
This study aimed to investigate the effect of the alcoholic extract of garlic and ginger together on the levels of glucose, peptide -c and body weight in diabetic white mice. The study included 40 male white mice, Balb/c strain, which were divided into four experimental groups (10 mice in each group). The first group was a physiological control that was injected with physiological saline (0.9%) until the end of the experiment. As for the second group, diabetes was induced with a dose of 200 mg/kg of Alloxan hydrate weight of the mouse only, while the third group developed diabetes, and then it was treated with alcoholic extract of garlic and ginger together at a dose of 500 mg/kg of mouse weight for 10 days. While the fourth group developed diabetes and was treated with Glibenclamide. At the end of the experiment, the animals were anesthetized and blood was drawn from them by cardiocentesis. The results showed the effectiveness of garlic and ginger extracts in reducing blood glucose concentration by 35.75% and returning Peptide-c levels to their normal levels, equivalent to Glibenclamide (glyburide), which is known as an oral hypoglycemic agent.